Encyclopedia of the philosophy of law and social philosophy - Sellers, M. N. S.; Kirste, Stephan (Springer, 2019)
This encyclopedia covers all topics in the philosophy of law and social philosophy, including the history, theory, and leading theorists of the philosophy of law and social philosophy. Featuring specially commissioned entries by an international team of the world's best scholars, including 2000-plus entries ensuring its place as the definitive reference work on the Philosophy of Law and Social Philosophy for the foreseeable future. The encyclopedia provides: 1) a clear concise expert definition and explanation of the key concepts in the field, written by leading scholars; 2) an essential reference for experts and newcomers alike, with entries ranging from short definitions of key terms to extended explorations of major topics; 3) an investigation of questions that have traditionally defined the field, but also more recent developments, significantly updating the fields of the philosophy of law and social philosophy; 4) introductions to theories and research that have developed globally